Palm Oil Fly Ash (POFA) as a Cementitious Material in Biomass Concrete: A Feasibility Review - Yong, Yoong Kee; Lee, Hoong Pin (INTI International University, 2022)
This review discussed the feasibility of using palm oil fly ash (POFA) as a cementitious material for partially replacing cement in producing concrete. Such an application is known to mitigate the emission of carbon dioxide (CO2). Meanwhile, POFA is one of the general wastes generated from palm oil mills, and it is conventionally disposed of via landfills. Thus, using POFA to generate concrete could mitigate the depletion of raw material, i.e., limestone, used for cement.